Estimation of Crown Fuel Load of Suppressed Trees in Non-treated Young Calabrian Pine (Pinus brutia Ten.) Plantation Areas - BAYSAL, İsmail; YURTGAN, Mehmet; KÜÇÜK, Ömer; ÖZTÜRK, Nuray (Kastamonu University, 2019)
Aim of study: Pinus brutia is the most widespread conifer forest tree species in Turkey. It is mainly distributed in fire sensitive regions of the country. The economic importance in wood production and the deterministic role in forest fires fighting activities make this forest tree more valuable and important. This study describes crown fuel load of suppressed trees in non-treated young Calabrian pine stands. Area of study: The study area is located in the Western Black Sea region of Turkey. Sampling plots were located in Hacımahmut Forest Planning Unit. Material and methods: Trees were selected from non-treated young Calabrian pine plantation stands and used to obtain live crown fuel load and characteristics. For this purpose, 30 young suppressed trees were cut and sampled. Main results: In sampled trees, oven dried total live needle biomass ranged between 0.54 kg and 3.19 kg and total live crown fuel load chanced between 1.96 kg and 12.73 kg. Regression models to estimate crown fuel load were developed according to some tree characteristics. Models developed explained 0.79 to 0.89% of the observed variation. Highlights: Regression analysis indicated that the total live crown fuel load was strongly correlated with both diameters at breast height (DBH) and crown base height (CBH).
Keywords: [No Keywords]